Matching Perspectives of Refugees and Voluntary Sports Clubs in Germany - Fingerle, Michael; Röder, Mandy; Olmesdahl, Kim; Haut, Jan (Italian Sociological Review, 2021)
In recent years thousands of refugees from the Middle East and Africa have moved to Europe. Many of them have experienced extremely stressful events and suffer, amongst other things, from lack of social relationships. Policy makers do often convey the impression that voluntary sports clubs (VSCs) can easily help to deal with these issues, as they provide broad offers matching every person’s individual needs. With only few exceptions, research has focused on the view of VSCs and their officials, but mostly left out the perspectives of refugees themselves, especially those outside organized sports. Thus, the focus of the present contribution is on the mutual fit between refugees’ expectations and the offers that sports organizations have. Following a socio-ecological perspective, data from a research project will be used to illustrate both perspectives. Refugees were asked about hindering conditions for participating in sports. In addition, functionaries of sports organizations were asked to answer survey questions regarding the efforts that sports organizations make to include refugees. The results reveal that the majority of the refugees had already actively participated in sports offers in their countries of origin. After arriving in Germany, the sporting habits changed, mostly due to organizational and financial reasons. With respect to functionaries we found that the idea that sport is integrative per se is widely believed in the field.